Bilimsel Toplantı Duyuruları - Adli Tıp Uzmanları Derneği ATUD (Adli Tıp Bülteni, 2000)
BİLİMSEL TOPLANTI DUYURULARI FUTURE EVENTS 1 9 Joint Meeting with the Forensic Science Service: - Crimes of the Millennium. .3-5 November 2000. Stakis Hotel, Bromsgrove, Birmingham. Convener; Mike Loveland. Details from Forensic Science Society Office. Tel: 01423 306068 2 Crime Scene Technology Workshop 2 A Crime Scene Practicum November 6-10, 2000 Evanston, IL Contact: Registrar Northwestern University. Traffic Institute 403 Church St. Evanston, IL 60201 (800) 32.3-4011 3 AFIS Curriculum November 13-13, 2000 Youngsville, NC Instructors: Marty Lucias, Johnny Leonard Contact: Clara Carroll Sirchie Fingerprint Labs, Inc. 100 Hunter Place Youngsville, NC 27396 (800) 336-7311 4 Crime Scene Technology Workshop 3 Advanced Techniques November 13-17, 2000 Evanston, IL Contact: Registrar Northwestern University, Traffic Institute 403 Church St. Evanston. 11. 60201 (800) .323-4011 3 Investigative Photography Workshop I Comprehensive Photographic Techniques December 4-8, 2000 Evanston, IL Contact: Registrar Northwestern University, Traffic Institute 403 Church St. Evanston, II. 60201 (800) 323-4011 6 Investigative Photography Workshop 2 Advanced Techniques December 11-13, 2000 Evanston, IL Contact: Registrar Northwestern University, Traffic Institute 403 Church St. Evanston, IL 60201 (800) 323-4011 7 Bloodstain Evidence Workshop I The Significance of Bloodstain Evidence in Death Scene Investigations December 11-13, 2000 Evanston. II. Contact: Registrar Northwestern University. Traffic Institute 403 Church St. Evanston, IL 60201 (800) .323-4011 8 One Hundred Years of Fingerprint Detection and Identification June 16-30, 2001 London, Great Britain Contact: Maurice Garvie or David Smith New Scotland Yard The Broadway London, SW1H0BG Great Britain 9 International Assoc, for Identification Annual Conference July 22-28, 2001 Dorai Resort, Miami. FL Contact: Candy Murray 20601 Netherland St. Orlando, FL .328.33 (407) 368-7-1.36 cc inference® t heia i .org